PERTUMBUHAN SEMAI EBONI (Diospyros celebica Bakh.) PADA BERBAGAI INTENSITAS CAHAYA DAN PENYIRAMAN - Sutejo, Bambang; Wardah, wardah; Zulkaidah, Zulkaidah (Universitas Tadulako)
Diospyros celebica Bakh is one of the strongest, one-class, beautiful types of wood, including high-value timber species and is a luxury wood species. The level of ebony regeneration in nature is relatively low, this is due to its semi-tolerant nature, which at the level of the ebony seedlings requires shade plants. Water is one physical component that is vital for plant growth and development. The role of water that is very important has the consequence that direct or indirect deficiencies or excess water in plants will affect all of its metabolic processes so that it can reduce plant growth. This research was conducted for 3 months, December 2015 until February 2016. The research location was located in the area of the Faculty of Forestry, Tadulako Palu University, Central Sulawesi Province. The experimental design used was the Factorial Completely Randomized Design (CRD), which consisted of two factors, namely light intensity and watering intensity. The results showed that the treatment of light intensity had a significant effect on the growth of ebony plants the best average growth results were found at 30% light intensity (C2). The treatment of watering intensity significantly affected the growth of Diospyros celebica Bakh, the best growth rate was found in P2 (watering morning and evening). The interaction between light intensity and watering intensity has no significant effect, this is due to the state of light intensity, the soil moisture is still relatively the same, both during watering P1 and P2 so that the availability of water for photosynthesis is still available.Keywords: Diospyrros celebica Bakh, light intensity, watering